Ultrasound-assisted rapid synthesis of β-aminoketones with direct-type catalytic Mannich reaction using bismuth(III) triflate in aqueous media at room temperature - Ozturkcan, S. Arda; Turhan, Kadir; Turgut, Zuhal (SPRINGER INTERNATIONAL PUBLISHING AG, 2012)
An innovative, powerful, efficient and relatively rapid method was developed to synthesise various beta-aminoketone derivatives from cyclohexanone, substituted aromatic amines and aromatic or hetero-aromatic aldehydes via ultrasound-assisted direct-type catalytic Mannich reaction using bismuth(III) triflate in water. Good yields of the desired beta-aminoketones were obtained at room temperature by ultrasound-assisted reaction within 1-2 h. The major advantages of the proposed method are undemanding conditions, easy operation, low toxicity, shorter reaction time, anti selectivity and higher yields in comparison with conventional methods. (C) 2011 Institute of Chemistry, Slovak Academy of Sciences
Keywords: sonochemistry; beta-aminoketones; direct-type Mannich reaction; bismuth(III) triflate; green innovation; HIGHLY ENANTIOSELECTIVE SYNTHESIS; SOLVENT-FREE; AMINO KETONES; 3-COMPONENT; ESTERS; EFFICIENT; BENZALDEHYDES; IRRADIATION; MICROWAVE; OXIDATION; Chemistry